Preliminary study on effects of hiit-high intensity intermittent training in youth soccer players - Gaetano, R.; Rago, V. (Journal of Physical Education and Sport, 2014)
Soccer is a sport about situation, subject to many dependents variables like field, adversary, teammates, presence of ball and more. Aspects that significantly affecting the training in this sport are: conditional aspect, psychological and technical-tactical. This study is about the periodization, it means the division of training season in specific periods in order to clearly defined goals. Part of this periodizated training was characterized by High Intensity Intermittent Training (HIIT), such important in soccer as many team sports, characterized by phases of high oxygen consumption alternate by recovery series. The research was conducted on a sample of 20 male Soccer players of 16.8 ± 1 years old members of a Sub-18 team of Italian National League "Beretti". The athletes were divided into two groups according to their results of aerobic power detected by the Cooper test carried out at the beginning of the preparatory period: a group working with an higher internal load (90% HR), and another group performing the same, but holding a lower one (80% HR.). That division was made in such a way as to obtain the desired adaptations and improvements in both groups, because having different characteristics, and in such a manner as to not create high overloads that, producing lactate they would prevent the adaptations and improvements sought. This study shows us how the intermittent training leads to a significant increase in VO2max. The data collected were subjected to a statistical study that showed improvements in physical performance of the different athletes thanks to the use of Periodization method integrated to High Intensity Intermittent Training. Significant, according to the method of periodization, the gradual increase of the applied load which allows the central nervous system (CNS) to adapt and achieve improvements. The aim of this study was to compare effects and improvements of an HIIT in two groups of Youth Soccer Players with different fitness characteristics, monitoring the Maximum Oxygen Consumption (VO2max) as parameter of internal load.